Students` Perspective: Is Teacher Still Important in Tele Class? - Zaqy Mubarok (Universitas Muhammadiyah Semarang, 2017)
Teaching English in 21st century is totally different. It is not only deals with English for communication, but also for connecting someone to the cyber world. Students can learn English directly from their fingers tip using their smart phone. The relation between teacher and students has changed because of the use of technology in English language learning. Teacher and students live in a Technology-Enhanced Learning Environment (TELE) that makes students as Gen-Z. They are not only passive listening to the teachers explanation but also seeking their own knowledge using their application in the smart phone. Besides that, there are visual, auditory, kinesthetic, tactile, group, and individual students as one of the main concern in TEFL. Furthermore, they like to finish all the tasks as soon as possible and find the solution using search engine. In line with blended learning, technology allows learning to take place partly or holly online. Online instruction is built into the design of a course. Classroom instruction is often used to prepare students to be autonomous learners that make them be active in learning. This study will be conducted by using questionnaire, observation, and interview from the students perspective in TEFL blended learning class in Asian context. Are teachers still important in this kind of classroom?